Impact of Education on Student Nurses' Advocacy and Ethical Sensitivity - Nesime, Demirören (Nursing ethics, 2022)
The nursing literature emphasizes that there are still inadequacies, differences, and inconsistencies in the definition of nurses' advocacy role, and that nursing education plays an important role in educating nurses for patient advocacy. The aim of the present study is to determine the effects of advocacy education onsocial justice advocacy and ethical sensitivity. Pre-test, post-test, parallel group, randomized controlled study. The study was carried out on 80 undergraduate nursing students in Turkey. Students was divided into experimental (40) and control (40) groups. Experimental group received advocacy education cirruculum. Both groups were applied as Socio-Demographic Characteristics, as pre- test and post-tests Social Justice Advocacy Scale, and Moral Sensitivity Questionnaire. The data were statistically evaluated with, the chi-square test, Two-Way Anova. The study was approved by Selcuk University Faculty of Health Sciences Non-Interventional Clinical Research Ethics Committee (09.25.2019/1218). Written informed consent was obtained from all participants. The pre-test score of the intervention group and that of the control group were similar(p > 0.05). The study group's post-test score was significantly higher than its pre-test score and the post-test score of the control group “social justice advocacy skills” and “moral sensitivity Questionnaire.” In two-way analysis of variance in repeated measures, there was a significant main effect of the type of groups. The two-way ANOVA results in repeated measures showed that group-time interaction was significant. The advocacy education cirruculum the experimental group increased in the social justice advocacy knowledge, attitude and skills and moral sensitivity. The advocacy education cirruculum the experimental group increased the social justice advocacy skills and moral sensitivity. The Advocacy education cirruculum can be suggested to be integrated into the undergraduate nursing curriculum.